2015
DOI: 10.1371/journal.pone.0122035
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Patterns of Ant Diversity across a Mountain with Climatically Contrasting Aspects in the Tropics of Africa

Abstract: Factors that drive species richness over space and time are still poorly understood and are often context specific. Identifying these drivers for ant diversity has become particularly relevant within the context of contemporary global change events. We report on a long-term bi-annual (wet and dry seasons), standardized sampling of epigeal ants over a five year period on the mesic and arid aspects of an inselberg (Soutpansberg Mountain Range) in the tropics of Africa. We detail seasonal, annual and long-term tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 63 publications
0
25
0
1
Order By: Relevance
“…However, we found that the effects of distance to water in general were higher during the wet than the dry season. Seasonal variation in rainfall has been shown to influence invertebrate activity patterns, competitive interactions, and the availability of resources (Wolda, 1988), including in ants (Munyai & Foord, 2015). Our results suggest that rainfall increased rather than decreased the effect of distance to water on ant communities.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, we found that the effects of distance to water in general were higher during the wet than the dry season. Seasonal variation in rainfall has been shown to influence invertebrate activity patterns, competitive interactions, and the availability of resources (Wolda, 1988), including in ants (Munyai & Foord, 2015). Our results suggest that rainfall increased rather than decreased the effect of distance to water on ant communities.…”
Section: Discussionmentioning
confidence: 58%
“…Seasonal variation in rainfall has been shown to influence invertebrate activity patterns, competitive interactions, and the availability of resources (Wolda, 1988), including in ants (Munyai & Foord, 2015). Seasonal variation in rainfall has been shown to influence invertebrate activity patterns, competitive interactions, and the availability of resources (Wolda, 1988), including in ants (Munyai & Foord, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between season and elevation leads to a qualitative change in seasonal richness patterns. Contrastingly, ants along elevational gradients (Bishop et al ., ; Munyai & Foord, ) had similar richness patterns in both wet and dry seasons. The Cederberg mountains experience snowfall during the winter.…”
Section: Discussionmentioning
confidence: 84%
“…These results are in agreement with the findings of Keroumi, Naamani, Soummane, and Dahbi () who reported greater abundance and higher species richness of ants in the wet than dry season in an Argan forest of Morocco. Munyai and Foord () reported that ground‐dwelling ants are intolerant of cold conditions and are more active and abundant in the wet than dry season. Activities of ground‐dwelling ants are affected by food resource availability, temperature, moisture and solar radiation, whose influence declines in the dry season and increases in the wet season (Abhinandini & Venkatesha, ).…”
Section: Discussionmentioning
confidence: 99%
“…Each vegetation type was sampled in three replicates. Each replicate had ten pitfall traps laid in a 2 × 5 grid with 10 m spacing between adjacent pitfall traps as described by Munyai and Foord (). Replicates were randomly located in each vegetation type and were separated by at least 300 m. Replicates in the disturbed grassland straddled patches of alien plants and secondary grassland as previously described for this vegetation type.…”
Section: Methodsmentioning
confidence: 99%